Drug Perscription Patterns of Out Patient Medication for Older People Insured by Social Organization Insurance in Year 2009 - Khalil No Kohan Ahvazi; Robab Sahaf; Ahmad Ali Akbari Kamrani (University of Social Welfare & Rehabilitation Sciences, 2012)
Objectives: Life expectancy and adolescents’ increment, as a threat or opportunity attracted researchers’ attention. Studies show an increase in treatment expenditures and adults care needs in comparison to other age groups. The goal of this study has been evaluating of medicine prescription in Iranian SSO insured adolescents and comparison in adolescence groups. Methods & Materials: It has been a retrospective, descriptive-analytical-cross sectional study by evaluating of SSO insured out patients’ prescriptions during the Year 1388. The information includes basic pattern tables consist of Drug name, pattern of specific prescribed drugs, Mean price of specific prescribed drugs, Expenditure of specific prescribed drugs, pattern More prescribed drug groups based on ATC classification, pattern The most prescribed drug groups based on adolescents’ age groups, non-adolescent group and WHO’s separated adolescents’ age groups. Results: The prescribed pattern drugs mean in under and over 60 years old people showed meaningful difference (P<0.005). The prescribed pattern drugs mean in three groups of adolescents, also showed meaningful difference (P<0.001). In addition the expenditure mean of prescribed drugs in under and over 60 years old people and in three groups of adolescents shows meaningful difference as P<0.004 and P<0.001 respectively. Conclusion: Based on the results of this study, adolescence has direct and increasing effect on refers to physicians and pharmacies. Among the adolescents' groups the expenditure mean increases although the number of refers decrease with in age increasing. By determining the most prescribed medicines, prevention of chronic diseases could be possible by education and training of families.